Community responses to a novel house design: A qualitative study of "Star Homes" in Mtwara, southeastern Tanzania. - Salum Mshamu; Judith Meta; Bipin Adhikari; Salma Halifa; Arnold Mmbando; Hannah Sloan Wood; Otis Sloan Wood; Thomas Chevalier Bøjstrup; Nicholas P J Day; Steven W Lindsay; Jakob Knudsen; Jacqueline Deen; et al. (PLoS ONE)
Introduction To evaluate the impact of a novel design "Star Home" on the incidence of malaria, respiratory tract infections and diarrheal diseases among children, randomly selected households in Mtwara, Tanzania were offered a free, new Star Home. Drawing on longitudinal qualitative research that accompanied the Star Homes study, this article describes the experiences of residents and the wider community of living with these buildings. Methods A total of four rounds of face-to-face interviews were undertaken with residents of Star Homes (n = 37), control (wattle/daub) homes (n = 21), neighboring households n = 6), community members (n = 17) and community leaders (n = 6). The use of Star Homes was also observed over these four time periods between 2021 and 2023. Interviews were conducted in Swahili, transcribed, and translated into English for thematic analysis. Results Star Homes residents appreciated several aspects of the Star Homes, including overall comfort, access to water and electricity, and clean toilets. There were concerns about some design elements, such as poorly closing doors, stoves perceived as inefficient, and the façade, which was susceptible to rainwater ingress. The houses were not always used as intended by their developers, for example, residents were sleeping downstairs instead of upstairs because of cold floors or difficulties using the stairs. Star Homes residents described how the structures triggered praise but also envy from other community members. Conclusions The findings highlight the need for close attention to the use of novel design houses and careful sensitization around the potential benefits of dwellings to ensure that the intended health impacts of interventions are achieved.